Labor cost, government intervention, and corporate innovation: Evidence from China - Li, Jianqiang; Shan, Yaowen; Tian, Gary; Hao, Xiangchao (Journal of Corporate Finance, 2020)
We examine the inducement effect of labor cost on corporate innovation in emerging markets. To establish causality, we adopt a difference-in-differences approach, based on the variations generated by the passage of the new Labor Contract Law in China, as well as an instrumental variable approach. We find the inducement effect of labor cost is more pronounced for Chinese non-state-owned enterprises, firms without political connections, and firms with low labor productivity. Our results support the induced innovation hypothesis in that increases in wages will induce invention and technology adoption, but also suggest that government intervention through state ownership and political connections largely decreases this inducement effect. Our findings have implications for emerging markets regarding the transition from a low-cost labor development model to an innovation-driven growth model.